Fantastic hope ebook - Hamilton, Laurell K. (2020)
A collection of sixteen sci-fi and fantasy stories edited by #1 New York Times bestselling author Laurell K. Hamilton and author William McCaskey. A child’s wish for her father comes true. The end of the world has never been so much fun. Conquering personal demons becomes all too real. It’s not always about winning; sometimes it’s about showing up for the fight. It’s about loving your life’s work, and jobs that make you question everything. In this anthology, seventeen authors have woven together brand-new stories that speak to the darkness and despair that life brings while reminding us that good deeds, humor, love, sacrifice, dedication, and following our joy can ignite a light that burns so bright the darkness cannot last. Laurell K. Hamilton and William McCaskey are joined by Kevin J. Anderson, Griffin Barber, Patricia Briggs, Larry Correia, Kacey Ezell, Monalisa Foster, Robert E. Hampson, John G. Hartness, Jonathan Maberry, L. E. Modesitt, Jr., Jessica Schlenker, Sharon Shinn, M. C. Sumner, Patrick M. Tracy, and Michael Z. Williamson in this collection.